Answers

2015-07-13T06:42:51+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
(x+1)²
first term = x²
second term = 2x
last term = 1
⇨ (x²+2x+1)

(x+2)²
first term = x²
second term = 4x
last term = 4
⇨ (x²+4x+4)

(x+3)²
first term = x²
second term = 6x
last term = 9
⇨ (x²+6x+9)

(x+y)²
first term = x²
second term = 2xy
last term = y²
⇨(x²+2xy+y²)

you can also use the foil method
ex) (x+1)² = (x+1)(x+1)
f = the first term (x)(x) = x²
o = outer term (x)(1) = x
i = inner term (1)(x) = x
l = last term (1)(1) = 1
copy the first term, add the outer and inner term and copy also the last term so the answer is (x²+2x+1)

hope you understand my explanations.. i'm not good in explaining because i'm not a teacher..(^_^) AMEN AND GODBLESS YOU TOO AND YOUR FAMILY..
0